2020
DOI: 10.1021/acsabm.0c00026
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Outgrowth of Neurites on Graphene Oxide-Based Hybrid Electrospun Fibro-Porous Polymeric Substrates

Abstract: Fabrication of a surface-engineered electrospun scaffold having biomimetic properties like the extracellular matrix (ECM) is essential for neural tissue engineering. An electroconductive and elastomeric scaffold with aligned fibers acting as a substrate may have a great impact on the directional outgrowth of neurites. In this study, we have electrospun electrically conductive, polyurethane-based elastomeric and topographically aligned fibro-porous neural scaffolds. Adhesive proteins of the ECM are documented t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Moreover, Col/CSGO nanocomposite permits neurite branches and outgrowth of NS/PCs (Figure 9). These results are in consistent with those reported by Thampi et al, 64 in which GO thin films enhanced neurite extensions.…”
Section: Cell Viability Adhesion and Infiltrationsupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, Col/CSGO nanocomposite permits neurite branches and outgrowth of NS/PCs (Figure 9). These results are in consistent with those reported by Thampi et al, 64 in which GO thin films enhanced neurite extensions.…”
Section: Cell Viability Adhesion and Infiltrationsupporting
confidence: 94%
“…Furthermore, GO can provide not only a micro/nanostructure but also a unique physicochemical cue for the better cell material interface that induce cellular interaction. 59,64 NS/PCs are sensitive to nanostructured substrates and nano-scale features would increase protein attachment and cell adhesion. The results of the cells SEM images indicated that in the three-dimensional Col scaffold more cells were spherical and a few cells appeared with neurite outgrowth (Figure 9).…”
Section: Cell Viability Adhesion and Infiltrationmentioning
confidence: 99%
“…Here it was shown that neurite outgrowth of PC-12 cells presented superior results when in contact with the GO-coated PCU material in comparison to poly- l -lysine (PLL) coated material. It was revealed that while the mean neurite length was similar on both GO and PLL-coated surfaces, the profile of length of neurites, when classified by length, showed more lengthier neurites on the GO-coated scaffolds . This study presents a novel surface engineering technique for GO coating on polymeric material.…”
Section: Tissue Engineeringmentioning
confidence: 81%
“…Release of drug properties showed that the π–π stacking interaction between the TCH drug and GO improved the controlled release of TCH compared to control groups without GO present. An electrospun GO/polycarbonate urethane (PCU) scaffold has been studied for its use in neural tissue engineering applications . Here it was shown that neurite outgrowth of PC-12 cells presented superior results when in contact with the GO-coated PCU material in comparison to poly- l -lysine (PLL) coated material.…”
Section: Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation